Pengaruh E-Service Quality Terhadap Kepuasan Pelanggan Pada Aplikasi Tokopedia - Ardiyansyah, Avicko Bimo; Winarno, Alex (eProceedings of Management, 2024)
Tokopedia is one of the largest internet marketplaces in Indonesia. Due to the COVID-19 pandemic, digitalchannels have become very important, even for customers who have never shopped online before. This researchaims to examine and evaluate the relationship between electronic service quality and customer satisfaction with theTokopedia application. This research uses descriptive research strategies and quantitative methodology. The samplingprocedure uses purposive sampling, namely a non-probability sampling approach. The methods used for data analysisinclude descriptive analysis, simple linear regression analysis, and processing using SPSS version 23 software. Basedon descriptive research, the variables of customer satisfaction and electronic service quality are in the very goodcategory, with respective percentages of 71.8% and 70.4%. Based on the results of simple linear analysis, electronicservice quality influences consumer satisfaction with the Tokopedia application by 82.45%, while other variables suchas price, brand image and perceived value influence customer satisfaction by 17.55%.Keywords-e-service quality, customer satisfaction, e-commerce.